A note on the reducibility of linear differential equations with quasiperiodic coefficients - Xiaoping Yuan; Ana Nunes (International Journal of Mathematics and Mathematical Sciences)
The system x˙=(A+ϵQ(t))x, where A is a constant matrix whose eigenvalues are not necessarily simple and Q is a quasiperiodic analytic matrix, is considered. It is proved that, for most values of the frequencies, the system is reducible.